Effect of Adding Palm Kernel Meal Extract to Rations Using Microparticle Protein Sources On Fatty Meat and Carcass Weight of Broiler Chicken - Krismiyanto, Lilik; Yunianto, Vitus Dwi Yunianto Dwi; Suthama, Nyoman; Amanusa, Agritio (Bantara Journal of Animal Science, 2023)
The purpose of the study was to examine the effect of the addition of palm kernel meal extract (PKME) to rations using microparticle protein sources on fatty meat and carcass weight of broiler chickens. The experimental chickens used were unsexed CP707 strain broilers aged 8 days as many as 200 birds with an average body weight of 153.98 ± 4.41 g. Palm kernel meal extract as treatment material. Ration composition includes ground corn, rice bran, microparticle soybean meal, microparticle fish meal, CaCO3, premix, lysine and methionine. The study was arranged using a completely randomized design with 5 treatments and 4 replicates, each experimental unit was filled with 10 animals. The treatments applied are: T0=rations using protein microparticles/RPM, T1=RPM+PKME 0,2%, T2=RK+PKME 0,4%, T3=PKME+EBS 0,6% dan T4=PKME+EBS 0,8%. Parameters measured included fat digestibility, relative weight of abdominal fat, meat fat mass and carcass weight. Data were analyzed for variance at the 5% significance level, if there was a significant effect, Duncan's test was conducted at the 5% significance level. The results showed that the addition of EBS to rations using microparticle protein sources had a significant effect (p<0.05) on fat digestibility, relative weight of abdominal fat, meat fat mass and carcass weight of broiler chickens. The conclusion is that the addition of 0.8% palm kernel meal extract to rations using microparticle protein sources can reduce fat digestibility, relative weight of abdominal fat, meat fat mass and carcass weight of broiler chickens.